Performance evaluation of roof top solar photovoltaic systems in Tamilnadu - M. Aravindan; V. Balaji; V. Saravanan; M. Arumugam (Institute of Advanced Engineering and Science, 2019)
This manuscript reports the monitored performance results of roof top solar photovoltaic (PV) power plants in different parts of Tamilnadu, India. In this work, PV plants of capacities 84 kWp and 18 kWp located at Tirunelveli and Ranipet respectively in Tamilnadu are considered. During an eight month period, of September 2014 to April 2015, these plants had generated 43.99 MWh and 15.55 MWh units of electricity respectively. The average electricity production per day for the considered period of these plants is 181.74 kWh and 62.81 kWh respectively. The performance ratio (PR) of these plants PV1 and PV2 is found to be 0.52 and 0.86 respectively. The characteristics of poly crystalline PV modules and the performance of employed photovoltaic inverters are also analyzed.It is observed that external conditions like climate and bad weather significantly reduces the PV system output, whereas it reduces marginally due to inverter failure as observed from the values of energy yield and performance ratio of these plants. Online monitoring of PV plant with DC/AC line and phase voltages and current waveforms observed for the given day are also presented.